Exploring Academic Stress and Coping Experiences Among University Students During the COVID-19 Pandemic - Xin Ren; Valerie A. Sotardi; Cheryl Brown (Education Sciences)
The COVID-19 pandemic has significantly impacted and disrupted higher education worldwide, creating unprecedented challenges for university students. In New Zealand, universities operated under varying pandemic restrictions, requiring students to frequently transition between online and in-person learning. This distinctive context provides a valuable opportunity to examine students’ academic stress and coping strategies during these transitions. Grounded in the transactional model of Stress–Appraisal–Coping, this research investigates sources of academic stress, coping strategies, and their effectiveness among university students during the pandemic. A mixed-methods approach was employed, with 193 university students completing an online survey incorporating qualitative and quantitative components. The thematic analysis results indicate eight major sources of academic-related stress and three types of coping strategies. Hierarchical regression analysis revealed that proactive and assistance-seeking strategies were associated with effective stress management, while avoidant strategies were linked to poorer outcomes. However, the study is limited by a low response rate (39.68%), which may affect the generalisability of findings. The results underscore the importance of fostering adaptive coping mechanisms in university settings and highlight the need for targeted institutional support to enhance student wellbeing and resilience in the post-pandemic academic landscape.